Epigenetic modifications and emerging therapeutic targets in cardiovascular aging and diseases - Yurou Qiu; Qing Xu; Peichen Xie; Chenshuang He; Qiuchan Li; Xin Yao; Yang Mao; Xiaoqian Wu; Tiejun Zhang (Pharmacological Research)
The complex mechanisms underlying the development of cardiovascular diseases remain not fully elucidated. Epigenetics, which modulates gene expression without DNA sequence changes, is shedding light on these mechanisms and their heritable effects. This review focus on epigenetic regulation in cardiovascular aging and diseases, detailing specific epigenetic enzymes such as DNA methyltransferases (DNMTs), histone acetyltransferases (HATs), and histone deacetylases (HDACs), which serve as writers or erasers that modify the epigenetic landscape. We also discuss the readers of these modifications, such as the 5-methylcytosine binding domain proteins, and the erasers ten-eleven translocation (TET) proteins. The emerging role of RNA methylation, particularly N6-methyladenosine (m6A), in cardiovascular pathogenesis is also discussed. We summarize potential therapeutic targets, such as key enzymes and their inhibitors, including DNMT inhibitors like 5-azacytidine and decitabine, HDAC inhibitors like belinostat and givinotide, some of which have been approved by the FDA for various malignancies, suggesting their potential in treating cardiovascular diseases. Furthermore, we highlight the role of novel histone modifications and their associated enzymes, which are emerging as potential therapeutic targets in cardiovascular diseases. Thus, by incorporating the recent studies involving patients with cardiovascular aging and diseases, we aim to provide a more detailed and updated review that reflects the advancements in the field of epigenetic modification in cardiovascular diseases.